Living with Wolves : Affects, Feelings and Sentiments in Human-Wolf-Coexistence - Thorsten Gieser (transcript, 2024)
With their return to Germany, wolves leave their traces in personal feelings, in the atmospheres of rural landscapes and even in the sentiments and moods that govern political arenas. Thorsten Gieser explores the role of affects, emotions, moods and atmospheres in the emerging coexistence between humans and wolves. Bridging the gap between anthropology and ethology, the author literally walks in the tracks of wolves to follow their affective agency in a more-than-human society. In nuanced analyses, he shows how wolves move, irritate and excite us, offering answers to the primary question: What does it feel like to coexist with these large predators?